Breast cancer presentation and diagnostic delays in young women. Issue 1 (11th November 2013) - Ruddy, Kathryn J.; Gelber, Shari; Tamimi, Rulla M.; Schapira, Lidia; Come, Steven E.; Meyer, Meghan E.; Winer, Eric P.; Partridge, Ann H.
Abstract : BACKGROUND: Young women may experience delays in diagnosis of breast cancer, and these delays may contribute to poorer outcomes. METHODS: In a prospective, multicenter cohort study, women recently diagnosed with breast cancer at age ≤40 years were surveyed regarding their initial signs or symptoms of cancer and delays in diagnosis. Self delay was defined as ≥90 days between the first sign or symptom and a patient's first visit to consult a health care provider. Care delay was defined as ≥90 days between that first visit and the diagnosis of breast cancer. In a medical record review, tumor characteristics were assessed, including disease stage. Univariate and multivariate models were used to assess for predictors of self delay, care delay, and advanced stage in the self‐detected subset. RESULTS: In 585 eligible participants, the first sign or symptom of cancer was a self‐detected breast abnormality for 80%, a clinical breast examination abnormality for 6%, an imaging abnormality for 12%, and a systemic symptom for 1%. Among women with self‐detected cancers, 17% reported a self delay, and 12% reported a care delay. Self delays were associated with poorer financial status ( P = 0.01). Among young women with self‐detected breast cancers, care delay was associated at trend level ( P = .06) with higher stage in multivariate modeling. CONCLUSIONS: Most young women detect their own breast cancers, and most do not experience long delays before diagnosis. Women with fewer financial resources are more likely to delay seeking medical attention for a self‐detected breast abnormality. Cancer 2014;120:20–25 . © 2013 American Cancer Society . Abstract : Eighty percent of women diagnosed with breast cancer at age ≤40 years detect their own breast abnormalities. Among women with self‐detected breast cancers, 17% report a delay of at least 90 days before they visit a health care provider for an evaluation, and 12% report a delay of at least 90 days between that visit and their diagnosis.